Light Metals 2017 - Ratvik, Arne P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2017 collection includes papers from the following symposia: Alumina and Bauxite Aluminum Alloys, Processing, and Characterization Aluminum Reduction Technology Cast Shop Technology Cast Shop Technology: Recycling and Sustainability Joint Session Electrode Technology The Science of Melt Refining: An LMD Symposium in Honor of Christian Simensen and Thorvald Abel Engh.
copper inserts and an innovative busbar network layout -- Minimizing Cathode Voltage Drop by Optimizing Cathode Slot Design -- Part 16: Aluminum Reduction Technology: Potroom Operations -- Crane Electrical Isulation Monitoring in Potlines: New CANDI 4.0 Development -- Surviving an Extended Power Outage after a Break Down in the Sub Station -- Retrofit of Damaged Corner Risers by Means of Bolted Connections -- Theory and Practice of High Temperature Gas Baking Technology for Alumninium Electrolysis Cells -- Part 17: Aluminum Reduction Technology: Technology Development -- IMPLEMENTATION OF D18+ CELL TECHNOLOGY AT EGA JEBEL ALI SMELTER -- Integrating a New Smelter Supervision HMI in Existing Control Systems at ALBRAS -- DX+ ULTRA - EGA HIGH PRODUCTIVITY, LOW ENERGY CELL TECHNOLOGY -- Potroom HF Emission Reduction by Anode Inert Tray Technology Performances of ALRO Industrial 1st of Class -- Enabling efficient heat recovery from aluminium pot gas -- The Successful Implementation of AP40 Technology at Kitimat -- Part 18: Cast Shop Technology: Continuous Strip Casting -- Effect of grain refiners on aluminum twin roll casting process -- Influence of Process Conditions on Segregation Behavior in Twin-Roll Casting of an AlFeSi alloy -- Effect of Magnesium Content on Microstructure and Mechanical Properties of Twin-Roll Cast Aluminum Alloys -- Influence of sticking on the roll topography at twin-roll casting of aluminum alloys -- Material Surface Roughness Change in Twin Roll Casti.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering